Human visceral and subcutaneous adipose stem and progenitor cells retain depot-specific adipogenic properties during obesity - Mathur, Neha; Severinsen, Mai C. K.; Jensen, Mette E.; Naver, Lars; Schrölkamp, Maren; Laye, Matthew J.; Watt, Matthew J.; Nielsen, Søren; Krogh-Madsen, Rikke; Pedersen, Bente Klarlund; Scheele, Camilla (Frontiers in Cell and Developmental Biology, 2022)
Abdominal obesity associates with cardiometabolic disease and an accumulation of lipids in the visceral adipose depot, whereas lipid accumulation in the subcutaneous depot is more benign. We aimed to further investigate whether the adipogenic properties where cell-intrinsic, or dependent on a depot-specific or obesity-produced microenvironment. We obtained visceral and subcutaneous biopsies from non-obese women (n = 14) or women living with morbid obesity (n = 14) and isolated adipose stem and progenitor cells (ASPCs) from the stromal vascular fraction of non-obese (n = 13) and obese (n = 13). Following in vitro differentiation into mature adipocytes, we observed a contrasting pattern with a lower gene expression of adipogenic markers and a higher gene expression of immunogenic markers in the visceral compared to the subcutaneous adipocytes. We identified the immunogenic factor BST2 as a marker for visceral ASPCs. The effect of obesity and insulin resistance on adipogenic and immunogenic markers in the in vitro differentiated cells was minor. In contrast, differentiation with exogenous Tumor necrosis factor resulted in increased immunogenic signatures, including increased expression of BST2, and decreased adipogenic signatures in cells from both depots. Our data, from 26 women, underscore the intrinsic differences between human visceral and subcutaneous adipose stem and progenitor cells, suggest that dysregulation of adipocytes in obesity mainly occurs at a post-progenitor stage, and highlight an inflammatory microenvironment as a major constraint of human adipogenesis.